Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12884-023-05818-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between hypertensive disorders during pregnancy and maternal and neonatal outcomes: a retrospective claims analysis

Abstract: Background Hypertensive disorders during pregnancy continue to increase in prevalence and are associated with several adverse outcomes and future cardiovascular risk for mothers. This study evaluated the association of hypertensive disorders compared to no hypertension during pregnancy with neonatal and maternal outcomes. We then evaluated risk factors associated with progression from a less to more severe hypertensive disorder during pregnancy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It is information that can add to the description of the disease now and or that influences the management of the patient. Many factors cause an increased incidence of preeclampsia in pregnant women, including a history of chronic hypertension, diabetes mellitus or kidney disease [58]. Pregnancy-induced hypertension, like preeclampsia, is one of the primary causes of death.…”
Section: Crosssectionalmentioning
confidence: 99%
See 1 more Smart Citation
“…It is information that can add to the description of the disease now and or that influences the management of the patient. Many factors cause an increased incidence of preeclampsia in pregnant women, including a history of chronic hypertension, diabetes mellitus or kidney disease [58]. Pregnancy-induced hypertension, like preeclampsia, is one of the primary causes of death.…”
Section: Crosssectionalmentioning
confidence: 99%
“…More severe hypertension diseases were associated with a higher risk of using a newborn intensive care unit (OR:2.41 for preeclampsia, OR:4.87 for superimposed preeclampsia). The two factors most likely to predict the progression from gestational or chronic hypertension to preeclampsia or superimposed preeclampsia were obesity or overweight and a history of preeclampsia during a previous pregnancy [58].…”
Section: Crosssectionalmentioning
confidence: 99%
“…Bromfield, SG et al (2023) 7 showed mothers and neonates born to mothers with preeclampsia or superimposed preeclampsia experienced more adverse outcomes compared to those without hypertension. Mothers and neonates born to mothers with gestational hypertension had outcomes similar to those without hypertension.…”
Section: Respondencesmentioning
confidence: 99%